Dermatoglifos technique: a trainer tool, physical and professional educator of physical activity, to detect sports talents (Impetus, 2021)
The sports selection processes for the detection of talents; historically it has used field and laboratory techniques to recognize the physical abilities, body structure and motor footprint. For decades, the incursion of the biomedical sciences, particularly genetics, opened the field of study of the dermatoglyphic, as a technique that allows recognizing the genetic components of the individual and their relationship with their physical abilities. This technique has been growing and becomes an accurate low-cost tool for coaches, physical education teachers and related professionals who use physical activity as a means of human interaction with their environment. The coaches find in the dermatoglyphic technique an additional ally to achieve competitive groups that reach high levels of recognition in sports. The document presents the basic dermatoglyphic technique used by the hotbed of research, for it can be used in different environments as a useful and reliable tool in selection processes.